Salvage radiotherapy for recurrent hypopharyngeal and laryngeal squamous cell carcinoma (SCC) after first-line treatment with surgery alone: a 10-year single-centre experience - Akbaba, Sati; Held, Thomas; Uzun-Lang, Kristin; Hörner-Rieber, Juliane; Plath, Karim; Forster, Tobias; Rieken, Stefan; Plinkert, Peter K.; Debus, Jürgen; Adeberg, Sebastian (Radiation oncology, 2019)
Salvage surgery of recurrent hypopharyngeal and laryngeal squamous cell carcinoma (SCC) results in limited local control and survival rates. As a result of recent technological progress, radiotherapy (RT) has become a valuable, potentially curative therapeutic option. Thus, we aimed to determine prognostic factors for survival outcome in order to optimize patient selection for salvage radiotherapy after failure of first-line treatment with surgery alone in this special patient cohort.